2019
DOI: 10.1186/s12913-019-4361-1
|View full text |Cite
|
Sign up to set email alerts
|

French cross-cultural adaptation of the Organizational Readiness for Implementing Change (ORIC)

Abstract: Background Organizational readiness is a factor known to influence the predisposition of individuals within an organization to change. Based on Weiner’s organizational theory, the “Organizational Readiness for Implementing Change” (ORIC) questionnaire was developed and validated to measure organizational readiness in healthcare contexts. However, no such tools allow French-speaking organizations to measure this concept. The objectives of this study were to (1) conduct a French cultural adaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
(47 reference statements)
0
14
0
2
Order By: Relevance
“…The original English ORIC measure is a brief measure with good psychometric properties, 42 which were confirmed in Danish 44 and French 45 validation studies. The study at hand aimed to translate the ORIC into German and assess its psychometric properties.…”
Section: Discussionmentioning
confidence: 86%
“…The original English ORIC measure is a brief measure with good psychometric properties, 42 which were confirmed in Danish 44 and French 45 validation studies. The study at hand aimed to translate the ORIC into German and assess its psychometric properties.…”
Section: Discussionmentioning
confidence: 86%
“…In all contexts, the importance and capacity of the instrument to measure the degree to which workers were able to implement changes in health services was observed. Similar to other studies 2,7,8 , item 1 was excluded from the ORIC-Br instrument because it did not present adequate compliance with the EFA 22 (Appendix 2). In the final version with 11 items, after the exclusion of item 1 from the pre-test version, the new arrangement of questions in the ORIC-Br instrument showed that items 1, 3, 5, 8 and 10 measured commitment and items 2, 4, 6, 7, 9 and 11 measured effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…At the organizational level, the construct is defined as a shared psychological state in which the organization members feel committed and confident about their collective skills for implementation 2 . This collective level, which transcends individuals, is often measured in two main dimensions: commitment and effectiveness 1,2,[6][7][8] . RESUMO: Objetivo: Avaliar o grau em que profissionais da atenção primária e organizações de saúde estão prontos para implementar mudanças nos serviços de saúde, principalmente no que se refere à implementação de novas tecnologias, políticas públicas ou programas de inovação, que merecem especial atenção.…”
Section: Introductionunclassified
“…It would seem that "readiness" to adopt innovative interventions may be a key element of a "culture of prevention" (Ruest et al 2019;Shea et al 2014;Storkholm et al 2018).…”
Section: Review Of Articles On the Culture Of Preventionmentioning
confidence: 99%